Immunomodulatory Effects of the Somatic Antigens of Fasciola Hepatica and Teladorgasia Circumcincta in Mice Immunized with Sheep Red Blood Cells - Ali Moradian; Seyyed Meysam Abtahi Froushani; Bijan Esmaeilnejad (Fasa University of Medical Sciences, 2021)
Background & Objective: Infestation of humans with helminth parasites can reduce the severity of some auto-inflammatory symptoms in humans. This study was done to evaluate the impact of the somatic antigens extracted from Fasciola hepatica (as an indicator Trematode) ,and Teladorgasia circumcincta (as an indicator nematode) on the immune responses of NMRI mice challenged with sheep red blood cells (SRBCs). Materials & Methods: The mice in treatment groups were intraperitoneally immunized with 1×109 SRBCs twice with 14 days intervals. Concurrent with the immunization, the mice received the extract of each of the parasites (50,100. And 150 µg of protein) or placebo, throughout the study on a daily basis. The specific cellular immune responses and the anti-SRBC antibody titers were detected by footpad thickness and, microhemagglutination test, respectively. Splenocytes were also monitored for cytokine production, proliferation rate, and respiratory burst. Results: The extracts of F. hepatica and T. circumcincta had an opposite effect on the change of the Anti-sRBC antibody level. The extract of F. hepatica caused a significant decrease in the antibody level whereas, extract T. circumcincta did not show any significant changes in the anti-SRBC antibody. Both extracts caused a significant decrease in the level of delayed-type hypersensitivity. However, the extract of F. hepatica caused a more profound reduction in the severity of delayed-type hypersensitivity. The level of IFN-γ in the splenocytes of immunized mice receiving the F. hepatica showed a more pronounced decrease than the immunized mice receiving the extract of T. circumcincta extract. IL-10 levels were only increased in the immunized mice that received the extract of F. hepatica. Conclusion: The extract of F. hepatica may have an immunosuppressive property, while the extract of T. circumcincta may have immunomodulatory properties.   Keywords: